2017
DOI: 10.1002/jsid.605
|View full text |Cite
|
Sign up to set email alerts
|

An observer‐metamerism sensitivity index for electronic displays

Abstract: The effect of observer metamerism induced by electronic displays depends to a large extent on their primary spectra (red, green, and blue in the most common case). In particular, for narrow‐band primary spectra whose peak wavelength lies in the range of high variability of the observer's color‐matching function, some observers can experience very large differences between actual surface colors (e.g. in a light booth) and displayed colors if the monitor is optimized for the International Commission on Illuminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Moreover, changing the primary set was also found to cause observer metamerism, a phenomenon that the color appearance of a pair of color stimuli composed of two primary sets appear to match to one observer, but mismatch to other observers. It was found that the degrees of observer metamerism (i.e., the variations of color differences perceived by different observers) varied with the primary sets [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, changing the primary set was also found to cause observer metamerism, a phenomenon that the color appearance of a pair of color stimuli composed of two primary sets appear to match to one observer, but mismatch to other observers. It was found that the degrees of observer metamerism (i.e., the variations of color differences perceived by different observers) varied with the primary sets [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this type of CMFs database, metrics have been developed to characterize the OM of displays with a single average value of a set of colors [20] and displaying distributions of OM over the color gamut [21]. Another quantitative approach to assess the effect of OM with a single value is based on the principal angles between the vector subspaces spanned by the display primaries multiplied with the 2-CMF1931 and a dataset of individual observers [22,23].…”
Section: Related Workmentioning
confidence: 99%
“…Most existing metrics used to quantify observer metamerism 13‐20 are proposed based on three‐ and four‐primary‐based displays or projectors. Combination RGI (red, green, indigo) of the constructed system is the primary combination most similar to typical LCD/LED displays: the chromaticity coordinates of R is (0.69, 0.31), which is very close to sRGB red (0.64, 0.33); and the G (0.22, 0.71) is almost exactly the AdobeRGB green (0.21, 0.71); the I (0.15, 0.05) is almost exactly the blue of sRGB (0.15, 0.06).…”
Section: Metamer Generatormentioning
confidence: 99%